Digital Natives, Digital Immigrants Part 2: Do They Really Think Differently? - Prensky, Marc (On the Horizon, 2001)
Part 2 of Prensky’s paper exploring the differences between “digital natives” and “digital immigrants”. In this second part the author presents evidence to support these differences from neurology, social psychology and from studies done on children using games for learning.
Publisher: MCB UP Ltd
Keywords: Culture; Language; Psychology; Students; Technology